2021
DOI: 10.1038/s41467-021-26812-9
|View full text |Cite
|
Sign up to set email alerts
|

A modular toolbox to generate complex polymeric ubiquitin architectures using orthogonal sortase enzymes

Abstract: The post-translational modification of proteins with ubiquitin (Ub) and Ub-like modifiers (Ubls) represents one of the most important regulators in eukaryotic biology. Polymeric Ub/Ubl chains of distinct topologies control the activity, stability, interaction and localization of almost all cellular proteins and elicit a variety of biological outputs. Our ability to characterize the roles of distinct Ub/Ubl topologies and to identify enzymes and receptors that create, recognize and remove these modifications is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 58 publications
(99 reference statements)
0
49
0
Order By: Relevance
“… 10 A recent report employs orthogonal sortase variants and C-terminally mutated Ub monomers. 9 We hypothesized that the chimeric E1 could activate and load Ub oligomers to Ubc9, which would subsequently transfer the defined Ub chains onto a LACE-tag on a substrate protein ( Figure 3 d). This approach would make use of natural linkage-defined Ub chains, which are commercially available or can be readily prepared and purified to homogeneity using canonical linkage-specific E2s, E3s, and DUBs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 A recent report employs orthogonal sortase variants and C-terminally mutated Ub monomers. 9 We hypothesized that the chimeric E1 could activate and load Ub oligomers to Ubc9, which would subsequently transfer the defined Ub chains onto a LACE-tag on a substrate protein ( Figure 3 d). This approach would make use of natural linkage-defined Ub chains, which are commercially available or can be readily prepared and purified to homogeneity using canonical linkage-specific E2s, E3s, and DUBs.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, it complements the method of ubiquitylation of proteins bearing a Lys(ε-Gly–Gly) residue recently reported by Lang and co-workers, which introduces two mutations at the C terminus of Ub to convert it to a sortase-compatible sequence. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Lang and coworkers. 149 The sortases and the peptidyl asparaginyl ligases such as Butelase and OaAEP1 show the greatest promise for future applications in protein engineering. While ligases generated from proteases such as subtiligase have potential, their requirement for ester and thioester substrates and low specificity makes their application in protein engineering more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…They have subsequently expanded this work and demonstrated that the eSrtA(2A-9) and Srt5M are orthogonal enabling them to generate a range of complex tri-ubiquitin and mixed ubiquitin/SUMO scaffolds ( Scheme 6C ). 149 …”
Section: Orthogonal Activity Of Peptide Ligasesmentioning
confidence: 99%
See 1 more Smart Citation